RELEVANCE OF THE ISSUE OF DIAGNOSIS OF INFLAMMATORY DISEASES OF THE PHARYNGEAL TONSIL - Lutfullaev G.U.; Kobilova Sh.Sh.; Erkinov G‘.J.; Po‘latov B.N.; Xazratov A. A. (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Chronic inflammation of the middle ear is a highly prevalent disease. Dangerous consequences of chronic suppurative otitis media (CSOM) include hearing loss and the development of complications associated with the spread of the pathological process to the inner ear and even into the cranial cavity.